(untitled) (World Science, 2020)
The article discusses points of views on the organization and implementation of monitoring in the field of physical culture and sports, in particular in the system of highly qualified junior athletes training. The article presents consideration of the problems in monitoring of the long-term system of athletes training, based on a three-component innovative approach to the system of sports training, which will allow to carry out more competent and balanced scientific and methodological steps in managing the athletes training during the educational and training processes.